a
x = 2/3-2pierwiastki z 2 + 3/3 + 2pierwiastki z 2 = 2(3 + 2pierwiastki z 2 ) +
3(3 - 2pierwiastki z 2) / ( 3 - 2pierwiastki z 2 )( 3 + 2pierwiastki z 2) =
= 6 + 4pierwiastki z 2 + 9 - 6pierwiastków z 2 / 9 - 8 = 15 - 2pierwiastki z 2
y= 2pierwiastki z 2 - 15
x = 15 - 2pierwiastki z 2 = - ( 2pierwiastki z 2 - 15 )
y = -x liczby przeciwne
b
x = 3/pierwiastek z 5 - pierwiastek z 2 + 1/ pierwiastek z 5 + pierwiastek z 2 =
= 3( pierwiastek z 5 + pierwiastek z 2 ) + pierwiastek z 5 + pierwiastek z 2 /
( pierwiastek z 5 - pierwiastek z 2 ) ( pierwiastek z 5 + pierwiastek z 2 ) =
= 3pierwiastki z 5 + 3 pierwiastki z 2 + pierwiastek z 5 - pierwiastek z 2 /
5 - 2 = 4 pierwiastki z 5 + 2 pierwiastki z 2 / 3
x = 4 pierwiastki z 5 + 2 pierwiastki z 2 / 3
y = 6 pierwiastków z 2
nie są to liczby przeciwne